Reproducing the City of London's Institutional Landscape: The Role of Education and the Learning of Situated Practices by Early Career Elites. (July 2014) - Faulconbridge, James R; Hall, Sarah
In this paper we argue that postgraduate education forms an important, but hitherto neglected, element in the distinctive institutional landscape of the City of London. In particular, and drawing on research into early-career financial and legal elites in the City, we show how postgraduate education tailored to the demands of employers within London plays an important role in indoctrinating early-career elites into situated, City-specific, working practices and, in so doing, helps to sustain the City's cultures and norms of financial practice. Specifying the role of postgraduate education in reproducing these situated City practices is significant because, although geographical variegation in working practices between international financial centres has been widely reported, less attention has been paid to how such institutionally embedded differences are created and sustained. By identifying education as one mechanism of creation and sustenance, our analysis enhances understanding of how the institutional landscapes that underlie financial centres might be maintained or, when necessary, challenged; challenge being significant in relation to attempts to reform practices and cultures in international financial centres in the wake of the 2007–08 crisis.